2019
DOI: 10.4081/mrm.2015.342
|View full text |Cite
|
Sign up to set email alerts
|

Weaning from tracheostomy in subjects undergoing pulmonary rehabilitation

Abstract: Background: Weaning from tracheostomy has implications in management, quality of life, and costs of ventilated patients. Furthermore, endotracheal cannula removing needs further studies. Aim of this study was the validation of a protocol for weaning from tracheostomy and evaluation of predictor factors of decannulation. Methods: Medical records of 48 patients were retrospectively evaluated. Patients were decannulated in agreement with a decannulation protocol based on the evaluation of clinical stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…20 Exact timing to perform tracheostomy procedure among intubated patients is the most debated aspect of tracheostomy. 16,21,22 In our study mean days of intubation before tracheostomy was 7 days. A meta-analysis by Adly et al, shows that in patients with prolonged intubation, tracheostomy done within 7 days of intubation significantly reduces the incidence of mortality and duration on mechanical ventilation.…”
Section: Discussionmentioning
confidence: 49%
“…20 Exact timing to perform tracheostomy procedure among intubated patients is the most debated aspect of tracheostomy. 16,21,22 In our study mean days of intubation before tracheostomy was 7 days. A meta-analysis by Adly et al, shows that in patients with prolonged intubation, tracheostomy done within 7 days of intubation significantly reduces the incidence of mortality and duration on mechanical ventilation.…”
Section: Discussionmentioning
confidence: 49%
“…We also found that 14 articles used objective examinations in the decannulation process, having five studies using nasolaringofibroscopia (11,18,20,22,31) , four using broncoscopia (20,27,28,35) , two using tomography (18,36) and three studies using swallowing videoendoscopy (15,18,26) . The use of the pulmonar (29) and manometry (31) function tests were less observed.…”
Section: Resultsmentioning
confidence: 83%
“…Three of the studies used medical records as a way of collecting data, and one study did not mention the members of the team. Luo et al (24) 44.57 4 17 X Berney et al (25) 47 15 29 X X X X Pandian et al (20) 58.07 18 39 X X X X Warnecke et al (26) 56.4 45 55 X X Hernández et al (27) 54.5 43 108 X X X Pryor et al (15) 53 44 82 X X X Cohen et al (22) 61.6 18 31 X X Mah et al (19) 55.1 144 249 X X X Zanata et al (9) 32.1 10 50 X Mathur et al (28) 22.67 12 18 X Kim et al (29) 47.6 7 55 ----Mitton et al (30) 52 41 65 X X X X Welton et al (16) 61 23 21 X X X X Pasqua et al (31) 64 21 27 ----Zanata et al (21) 53 4 16 X X Thomas et al (17) 71.4 36 86 X X X Tawfik et al (32) 48 57 38 ----Nakashima et al (33) 44.9 22 142 X Terra et al (34) 37.8 33 59 X X Schneider et al (35) 61.4 22 31 X X X Bianchi et al (11) 75 24 27 X X X Shrestha et al (36) 36 20 98 X X X -Budweiser et al (37) 70 46 120 ----Gundogdu et al (18) 29. Baseline disturbances data were also listed in the populations of each article (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations